Measurements of inclusive W plus jets production rates as a function of jet transverse momentum in p(p)over-bar collisions root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Arov, M.; et al. (Elsevier B.V., 2011)
This Letter describes measurements of inclusive W (-> ev) + n jet cross sections (n = 1-4), presented as total inclusive cross sections and differentially in the nth jet transverse momentum. The measurements are made using data corresponding to an integrated luminosity of 4.2 fb(-1) collected by the do detector at the Fermilab Tevatron Collider, and achieve considerably smaller uncertainties on W + jets production cross sections than previous measurements. The measurements are compared to next-to-leading order perturbative QCD (pQCD) calculations in the n = 1-3 jet multiplicity bins and to leading order pQCD calculations in the 4-jet bin. The measurements are generally in agreement with pQCD calculations, although certain regions of phase space are identified where these predictions could better match the data. (C) 2011 Elsevier B.V. All rights reserved.